Prioritizing the Intangibles among Management Graduates of an Educational Supply Chain; An AHP Approach - Haidar Abbas; Zaheer Ahmed Khan (International Journal of Supply Chain Management, 2017)
Soon after the introduction of liberalization and privatization in India around 1991, people started paying more attention towards management education (Gupta Satapathy, 2012). If one looks at the statistics, one will be surprised to see that earlier, there were only a handful of public and private sector universities and institutions offering degrees in management/business administration and related field. However, in the past one decade or so, the educational supply chain is flooded with new institutions coming forward with diverse specializations (Saha, 2012). It resulted in the waning down of those necessary intangibles which are considered indispensable prerequisites to enter the professional arena. Such intangibles would include the good communication skills, good knowledge of the world economy and its happenings, good command over subjects, good analytical skills, reasonable technical skills, disciplined and a pleasant personality etc. In the view of this problem, this research paper attempts a) to identify those broad intangibles desired by the job market and then, b) to establish priorities among them based on academicians perception. The first objective related to the identification of broad intangibles was met by extensive literature review and for the second one, the primary data were collected from four academicians and priorities were established using Analytical Hierarchy Process (AHP). Besides enriching the literature, the outcome of this study will help the aspiring management graduates understand a clear-cut hierarchy of the several desired attributes in terms of their perceived importance given.